2018
DOI: 10.1292/jvms.18-0240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cilostazol on the heart rate in healthy dogs

Abstract: Appropriate dosages of cilostazol have not been studied in veterinary patients, and the degrees of heart rate (HR) increase have not been studied in dogs administered cilostazol. Therefore, this study aimed to investigate the degrees of HR increase in healthy dogs administered cilostazol. Thirty healthy beagle dogs (15 males and 15 females; age, 5–8 years) were divided into 3 groups of 10 dogs each and orally administered 2.5, 5, or 10 mg/kg cilostazol (twice a day at 8:00 AM and 8:00 PM for 10 days). Higher H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
3
9
1
Order By: Relevance
“…The dosages and timing of administration of cilostazol were selected based on past case reports ( 12 , 13 ), basic research ( 21 ), and the experience of the attending veterinarian. The most frequently used dose of cilostazol was 10.0–10.9 mg/kg twice daily (20.0–21.8 mg/kg/day).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The dosages and timing of administration of cilostazol were selected based on past case reports ( 12 , 13 ), basic research ( 21 ), and the experience of the attending veterinarian. The most frequently used dose of cilostazol was 10.0–10.9 mg/kg twice daily (20.0–21.8 mg/kg/day).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, cilostazol may be an effective treatment for sinus bradycardia, sinus arrest, and SSS, all of which are arrhythmias caused by sinus node dysfunction. We have previously demonstrated that cilostazol significantly reduces the PQ interval in dogs, which indicates that this agent influences AV conduction time but not the QT interval ( 21 ). Therefore, cilostazol may be effective in patients with maintained AV conduction or in patients with abnormal but not yet completely disrupted AV conduction.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…14 The abovementioned evidence indicates that cilostazol can be used to treat bradyarrhythmia. Although, cilostazol has been reported to increase the heart rate in healthy dogs, 15 and successfully treat sick sinus syndrome in a dog, the use of cilostazol has not been reported in cats. 16 The present study describes the clinical course and histological findings in a cat with high-grade AV block treated with cilostazol.…”
Section: Long-term Management Of High-grade Atrioventricular Block Usmentioning
confidence: 99%